Peningkatan Pertumbuhan Ekonomi Melalui Pengembangan Sektor Unggulan di Kabupaten Jombang - Muhamad Fatihul Huda; Hendry Cahyono (Universitas Negeri Surabaya, 2021)
Abstract Economic growth is an important indicator in regional economic development. This research was conducted in Jombang Regency purpose to identify and analyze economic growth thought the leading sectors in Jombang Regency. This research uses descriptive quantitative research with a development planning model. The data used is time series data, namely the Gross Regional Domestic Product (GRDP) of Jombang Regency in 2015-2019. Data will be analyzed using Location Quotient Analysis (LQ), Shift Share (SS), Klassen Typology, and Overlay Analysis. The results of the analysis show that there are six leading sector in Jombang, namely the Construction Sector; Wholesale and Retail Trade, Cars and Motorcycles Repair Sector; Information and Communication Sector; Real Estate Sector; Education Service Sector; and other service sectors. Keywords: Leading Sectors, LQ, Shift Share, Klassen Typologi, Overlay Analysis